Teachers’ perceptions in training courses on talents/giftedness - Muglia Wechsler, Solange (2016)
Programs designed for teachers’ training should prepare them to attend to the needs of talented/gifted students in their classrooms. The purpose of this study was to investigate whether future teachers had sufficient knowledge to attend the talented/gifted students. The sample consisted of 170 undergraduate students (145 women, 25 men), who were enrolled in teachers’ preparation courses in 2 private and 3 state universities in Brazil. A questionnaire with six open questions about talent/giftedness was administered in a group setting, and answers were classified by content analysis. The results indicated that teachers have several doubts about these concepts and question if they are responsible or the school administrators are responsible to attend to these students. In conclusion, future teachers are not receiving adequate preparation to guide talented/gifted students in their classrooms.